The Owners of Kinship Asymmetrical Relations in Indigenous Amazonia - Costa, Luiz (Malinowski Monographs, 2018)
The Owners of Kinship investigates how kinship in Indigenous Amazonia is derived from the asymmetrical relation between an "owner" and his or her dependents. Through a comprehensive ethnography of the Kanamari, Luiz Costa shows how this relationship is centered around the bond created between the feeder and the fed.Building on anthropological studies of the acquisition, distribution, and consumption of food and its role in establishing relations of asymmetrical mutuality and kinship, this book breaks theoretical ground for studies in Amazonia and beyond. By investigating how the feeding relation traverses Kanamari society-from the relation between women and the pets they raise, shaman and familiar spirit, mother and child, chiefs and followers, to those between the Brazilian state and the Kanamari-The Owners of Kinship reveals how the mutuality of kinship is determined by the asymmetry of ownership.